The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1152/ajpgi.00472.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of endogenous ATP7A (Menkes protein) in intestinal epithelial cells: copper-dependent redistribution between two intracellular sites

Abstract: .-We report for the first time on the copper-dependent behavior of endogenous ATP7A in two types of polarized intestinal epithelia, rat enterocytes in vivo and filter-grown Caco-2 cells, an accepted in vitro model of human small intestine. We used high-resolution, confocal immunofluorescence combined with quantitative cell surface biotinylation and found that the vast majority of endogenous ATP7A was localized intracellularly under all copper conditions. In copper-depleted cells, virtually all of the ATP7A loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
144
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 68 publications
9
144
2
Order By: Relevance
“…MD is an X-linked copper deficiency disorder that arises due to mutation of ATP7A (OMIM 309400). The primary site of the defect are the intestinal enterocytes, which take up dietary copper, but absorption into the portal circulation is impaired due to defective ATP7A-mediated copper efflux (2,3). Consequently, systemic copper deficiency accounts for the wide range of neurological and developmental defects (1).…”
Section: Menkes (Md)mentioning
confidence: 99%
See 1 more Smart Citation
“…MD is an X-linked copper deficiency disorder that arises due to mutation of ATP7A (OMIM 309400). The primary site of the defect are the intestinal enterocytes, which take up dietary copper, but absorption into the portal circulation is impaired due to defective ATP7A-mediated copper efflux (2,3). Consequently, systemic copper deficiency accounts for the wide range of neurological and developmental defects (1).…”
Section: Menkes (Md)mentioning
confidence: 99%
“…ATP7A and ATP7B reside at the trans-Golgi network, where they receive copper from the copper chaperone ATOX1. With increased intracellular copper levels, ATP7A and ATP7B traffic to exocytic vesicles near the basolateral or apical membranes, respectively (2,3,5,6). When copper levels are restored, they recycle back to the trans-Golgi network (5).…”
Section: Menkes (Md)mentioning
confidence: 99%
“…Previously, most similar studies have focused on mammalian ATP7A regulation at the post-translational level and several of these studies have shown that the translocation of ATP7A from a compartment localized within the trans-Golgi network to a compartment near the plasma membrane is required for regulation of intracellular Cu levels (Nyasae et al, 2007;Lutsenko et al, 2008). Transcriptional regulation of ATP7A levels in liver and intestine of zebrafish and sea bream exposed to waterborne Cu (Craig et al, 2009;Minghetti et al, 2010) and in rat intestine after Cu-exposure (Bauerly et al, 2005) indicate an additional mechanism of regulation in Cu efflux.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The Cu-ATPases predominantly reside at the trans-Golgi network (TGN) under basal conditions for metallation of copper-dependent enzymes of the secretory pathway. In response to elevated intracellular copper levels, they traffic to vesicles located near the basolateral (ATP7A) (3,4) or apical (ATP7B) (5-7) membranes where they sequester and mediate export of the excess copper. When intracellular copper levels are restored, the Cu-ATPases recycle back to the TGN.…”
mentioning
confidence: 99%
“…In MD, a fatal X-linked copper deficiency disorder, the intestinal enterocytes are the primary site of the defect. Defective copper transport across the basolateral membrane of these cells into the portal circulation leads to a systemic copper deficiency with devastating consequences (3,4,9,10). Biochemical abnormalities lead to neurological and developmental defects among many other symptoms (9,11).…”
mentioning
confidence: 99%